Artificial Intelligence Applied to Medical Imaging and Computational Biology - Leonardo Rundo; Andrea Tangherloni; Carmelo Militello (Applied Sciences, 2022)
The Special Issue “Artificial Intelligence Applied to Medical Imaging and Computational Biology” of the Applied Sciences Journal has been curated from February 2021 to May 2022, which covered the state-of-the-art and novel algorithms and applications of Artificial Intelligence methods for biomedical data analysis, ranging from classic Machine Learning to Deep Learning [...]